Urgensi Seni Budaya Sebagai Estetika dalam Pendidikan Agama Islam - Milawati Milawati; Yazida Ichsan; Aisyah Luthfi Hasanah; Ria Nur Khasanah (Institut PTIQ Jakarta, 2022)
Art is a form of creative work that contains elements of beauty or aesthetics in it. This is in line with what was said by M. Quraish Shihab, where he said that art and culture is a form of expression of a creative work regarding the beauty of nature, life, every individual in a meeting that contains truth and beauty based on the perspective of Islam and based on human nature. The article, entitled Urgency of Cultural Arts as Aesthetics in Islamic Religious Education uses qualitative research methods, in which data collection utilizes literature study techniques, which utilize reading media such as books, newspapers, magazines, articles, and related journals. Where this research produces a link between education and cultural arts that cannot be separated, because both influence each other, including cultural arts that shape the personality of an individual or group. Because in the education process, the values of Islamic art and culture are taught in the teaching of Islamic Religious Education itself. Education is a cultural process, which in education will greatly affect human survival in religion, social and culture.